Implementation Of The Positive Culture Of Seven Days Of Special Education At SDN 1 Pasanggrahan - Nurhayati, Tita; Retnoasih, Agustina; Purwanto; Halimah, Lili (Forum Ilmu Sosial, 2024)
Education is the place where the seeds of culture are sown within society. Through the educational process, good character traits develop within individuals, equipping them to face life with physical and spiritual happiness. Education is a place for character formation. A positive culture involves good habits encompassing activities fostering students' character. The Government of Purwakarta Regency issued Regent Regulation Number 69 of 2015 on Education, laden with Sundanese philosophy through the "7 Poe Atikan Istimewa" (Seven Days of Special Education). This program features themed education with a different character-based theme daily and is implemented in schools across Purwakarta Regency. This study aims to describe and recognize the implementation of the positive culture of Seven Days of Special Education at SDN 1 Pasanggrahan. This research uses a qualitative method, with subjects being all students of SDN 1 Pasanggrahan from grades I to VI. Data collection methods include interviews, observations, and documentation. Based on the interactions between students and teachers and interviews with students, teachers, and the principal, the researchers describe ways to address student issues by implementing the positive culture of Seven Days of Special Education. This program, implemented by all primary and secondary education units in Purwakarta since 2015, effectively fosters a positive culture in schools, including at SDN 1 Pasanggrahan.